Caretakers' stated willingness to pay for children's spectacles in cross river state, Nigeria and its implication for a cross-subsidisation scheme: a cross-sectional study - Anne Effiom Ebri; Ciaran O'Neill; Kenneth Azubuike; Nathan Congdon; Christine Graham; Lynne Lohfeld; Ving Fai Chan (BMC, 2023)
Abstract Background Understanding caretakers' willingness to pay (WTP) for their children's spectacles is essential to improving the sustainability of refractive error services and spectacle provision. Therefore, we investigated the willingness of caretakers to pay for their children's spectacles in a multi-centre study to develop a spectacle cross-subsidisation scheme in the Cross River State (CRS), Nigeria. Methods We administered the questionnaire to all caretakers whose children were referred from school vision screenings to four eye centres for full refraction assessment and dispensing of corrective spectacles from 9 August to 31 October 2019. We collected information on socio-demography, children's refractive error types, and spectacle prescription and then asked the caretakers about their WTP for the spectacles using a structured questionnaire and bidding format (in the local currency, Naira, ₦). Results A total of 137 respondents (response rate = 100%) from four centres were interviewed: with greater proportion of women (n = 92, 67.1%), aged between 41 and 50 years (n = 59, 43.1%), government employees (n = 64, 46.7%) and had acquired college or university education (n = 77, 56.2%). Of the 137 spectacles dispensed to their children, 74 (54.0%) had myopia or myopic astigmatism (equal to or greater than 0.50D). The mean stated WTP for the sample population was ₦3,560 (US$ 8.9) (SD ± ₦1,913.4). Men (p = 0.039), those with higher education (p < 0.001), higher monthly incomes (p = 0.042), and government employees (p = 0.001) were more willing to pay ₦3,600 (US$9.0) or more. Conclusion Combining our previous findings from marketing analysis, these findings provided a basis to plan for a children's spectacles cross-subsidisation scheme in CRS. Further research will be needed to determine the acceptability of the scheme and the actual WTP.